THERMAL BEHAVIOR OF PYROLYSIS OIL - DIESEL OIL EMULSION IN EVAPORATING MICRONIC DROPLETS. Issue 2 (25th January 2022) - Calabria, Raffaela; Chiariello, Fabio; Massoli, Patrizio
ABSTRACT: Transformations inside emulsion droplets of 82 µm have been studied by using laser diagnostics. Arrays of calibrated droplets of emulsion 70/30 w/w diesel oil/pyrolysis oil were injected in pre-heated air flow inside a tubular reactor. Four thermal regimes have been studied: room temperature, 150°C, 250°C, and 350°C. For comparison, droplets of the diesel oil used to form the emulsion were studied in the same experimental conditions. The investigation has been performed by applying the Generalized Scattering Imaging laser technique that allows the simultaneous determination of size and optical properties of droplets. This optical diagnostic technique permitted to infer the chemical-physical changes inside the emulsion droplet by measuring the imaginary part of their refractive index. At 150°C and 250°C, the emulsion droplets suffered progressive depletion of the diesel oil phase. The pyrolysis oil, dispersed in the diesel oil matrix in the form of microdroplets 2 µm sized, underwent partial evaporation, liquid phase pyrolysis, and polymerization. At 350°C almost all the diesel oil had evaporated and the pyrolysis oil microdroplets dispersed in the emulsion droplet had merged to form a single droplet. These residual droplets showed a very narrow size distribution and an absorption coefficient greater than that of the original PO in agreement with the assessment that they represent the combined outcome of evaporation, liquid phase pyrolysis and polymerization of the pyrolysis oil. Samples of residual droplets were captured at the exit of the reactor and analyzed by means of optical microscopy. The microscope analysis was consistent with the laser diagnostics results.